2010
DOI: 10.1159/000320895
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Clinician Perceptions of Therapeutic Alliance as Predictors of Improvement in Depression

Abstract: Background: Meta-analyses have consistently concluded that a positive therapeutic alliance is associated with better clinical outcomes and progress. To date, however, very few studies have focused on sociodemographic or clinical patient characteristics as moderators of alliance. Method: A multicenter longitudinal treatment outcome study was conducted to investigate the associations of patient and clinician perceptions of the therapeutic alliance with improvement in depression, and to investigate whether these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 62 publications
0
26
1
3
Order By: Relevance
“…This confirms evidence from psychotherapy research of a stronger alliance-outcome relation when using patient-rated measures (Horvath and Symonds, 1991). In contrast, our finding that the rate of reduction of patient-rated unmet needs decelerated with higher patient-rated HA ratings was rather surprising at first, as previous research suggests that a better alliance is related to faster (De Bolle et al, 2010) or no change (Puschner et al, 2008) in subsequent clinical improvement. However, these studies used different alliance and outcome measures, and analyses applied absolute rather than mean-centered alliance scores.…”
Section: Does Alliance Predict Unmet Needs Over Time?contrasting
confidence: 94%
See 1 more Smart Citation
“…This confirms evidence from psychotherapy research of a stronger alliance-outcome relation when using patient-rated measures (Horvath and Symonds, 1991). In contrast, our finding that the rate of reduction of patient-rated unmet needs decelerated with higher patient-rated HA ratings was rather surprising at first, as previous research suggests that a better alliance is related to faster (De Bolle et al, 2010) or no change (Puschner et al, 2008) in subsequent clinical improvement. However, these studies used different alliance and outcome measures, and analyses applied absolute rather than mean-centered alliance scores.…”
Section: Does Alliance Predict Unmet Needs Over Time?contrasting
confidence: 94%
“…The large majority of studies investigating the alliance-outcome relation used crosssectional or two time-point data only, limiting causal inferences. An exception is a study which reported that patient-and staff-rated HA predicted subsequent clinical improvement when controlling for prior symptom change (De Bolle et al, 2010). Another study, using a multilevel model controlled for confounders, showed that a reduction in outcome (unmet needs) preceded an increase of the patient-, but not of the staff-rated HA (Junghan et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Research on the relationship psychiatrist- and patient-assessed alliance in pharmacotherapy is scant. Yet, in one study, both psychiatrist- and patient-assessed working alliances were predictive of outcome (De Bolle, Johnson, & Fruyt, 2010). Future pharmacotherapy research should use both patient and psychiatrist assessments of alliance to further tease apart whether there may be differences between the two modes of assessment.…”
Section: Discussionmentioning
confidence: 99%
“…While there is debate in the adult literature concerning if the client’s rating of TA is more predictive than the clinicians (De Bolle, Johnson, & De Fruyt, 2010; Horvath, 2001; Horvath, Del Re, Flückiger, & Symonds, 2011), in treatment with youth there is the added complexity of caregiver involvement in treatment (Green, 2009; Hawley & Garland, 2008). In the present study these three respondents’ (clinician, youth and caregiver) ratings of severity of mental health status (symptoms and functioning) are compared with three ratings of TA provided by them.…”
Section: Longitudinal Perspectives On the Therapeutic Alliance In Youthmentioning
confidence: 99%